Variações populacionais e intrapopulacionais de um pimelodídeo omnívoro : efeitos da dinâmica sazonal em uma planície de inundação Neotropical. - Fernandes, Alessandra (2015)
Although intra-population variation in niches is a widespread phenomenon in animal populations to fish these studies remain poorly understood. It is known that for these animals the individual variation in the use of resources can result from environmental differences in food availability, promoted by space and/or seasonal differences. Based on this, we investigated the populational and within-population variations in the diet of Pimelodus maculatus, in the dry and wet seasons in the lagoons of the Pantanal, Mato Grosso, Brazil. In the dry season the diet was based mainly on scale, fish and detritus while in wet season on fruit and seed, showing a significant difference. The trophic niche breadth values were relatively low and seasonally similar. High values of variation between individuals in the diet (E) and low values of the degree of clustering (Cws) regardless of season were found. The combination of these values showed that in the population there are specialists and generalists individuals indicating one nested diet. The median individual specialization index (PSi) was statistically lower in wet season, showing that individuals were more specialists. Thus, the seasonal availability of resources appears to be the main mechanism for the diet specialization in both population and individual level.